Examining The Impact Of Pandemic-Induced Changes On College Student Productivity: A Quantitative Analysis - Budiman, Muhammad Fathar Hamada (APPS Publications, 2021)
Objective – This research aims to reveal if there is any difference in college students’ productivity during and after the COVID-19 pandemic. This research will examine the factors that influence students’ productivity at those times. The factors that will be discussed are the learning environment, teaching methods, and students’ expectations. Methodology – Using Smart-PLS software as a tool to examine validity and reliability, this study is quantitative in nature and 124 students in all took part in the survey for this study. The present study was conducted via an online platform, specifically Google Forms, in order to collect data from participants in an anonymous manner. Findings – The result highlights the teaching methods affect academic performance, while learning environment and students’ expectations did not. Novelty – This study focuses on examining the impact of the COVID-19 pandemic on college students’ productivity and the specific factors that influence this change. While there have likely been studies on the general impact of the pandemic on education, this research specifically delves into the productivity aspect and isolates learning environment, teaching methods, and student expectations as key factors. This targeted approach provides valuable insights into how the pandemic has affected students’ academic performance and what factors can be attributed to these changes.